The Influence of Leader Member Exchange on Employee Performance with Work Engagement and Innovative Behaviour as Mediating Variables in OPD (Regional Device Organizations) Within The Pasuruan District Government - Prilatama, Aris; Murwani, F. Danardana; Winarno, Agung (Journal of Applied Business, Taxation and Economics Research, 2025)
The performance of government offices is strongly influenced by the performance of employees who are the spearhead of the organization. This research is quantitative research using descriptive and explanatory analysis. The sampling method used in this study uses probability sampling method with stratified random sampling method. The population in this study were all Pasuruan Regency Government Employees, with a minimum employee tenure of 1 (one) year and an employee age range of 20 - 56 years. The total population in this study was 343 Pasuruan Regency Government Employees. The number of samples in this study was determined using a sample size calculator so that what was obtained from the calculation was 217 samples as sample respondents in this study. Based on the results of the study showed that: (1) leader member exchange has a positive and significant effect on employee performance; (2) leader member exchange has a positive and significant effect on work engagement; (3) leader member exchange has a positive and significant effect on innovative behavior; (4) work engagement has a positive and significant effect on employee performance; (5) innovative behavior has a positive and significant effect on employee performance; (6) leader member exchange has a positive and significant effect on employee performance through work engagement; (7) leader member exchange has a positive and significant effect on employee performance through innovative behavior